Measurement of exclusive ρ0 ρ0 production in mid-virtuality two-photon interactions at LEP - Dova, María Teresa (2004)
Exclusive ρ0ρ0 production in two-photon collisions between a quasi-real and a mid-virtuality photon is studied with data collected at LEP at centre-of-mass energies 183 < √s < 209 GeV with a total integrated luminosity of 684.8 pb−1. The cross section of the process γ γ ∗ → ρ0ρ0 is determined as a function of the photon virtuality, Q2, and the two-photon centre-of-mass energy, Wγ γ , in the kinematic region: 0.2 < Q2 < 0.85 GeV2 and 1.1 < Wγ γ < 3 GeV.